Peningkatan Pengetahuan mengenai Analisis Kuantitatif pada Rekam Medis Elektronik di Rumah Sakit Umum Hidayah Boyolali - nugraheni, sri wahyuningsih; Eni Nur Rahmawati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Assessment of the quality of service in hospitals can be done by determining the completeness of filling in medical record documents through quantitative analysis. Quantitative analysis of medical record documents is the study or review of certain parts of the contents of medical records with the aim of finding specific deficiencies related to recording medical records. Quantitative analysis of medical records includes four review components, namely identification review, recording review, reporting review, and authentication review. Rumah Sakit Umum Hidayah Boyolali has implemented electronic medical records since January 2023 in accordance with the mandate of the Republic of Indonesia Minister of Health Regulation Number 24 of 2022 concerning medical records. The aim of PkM activities is to increase the knowledge and abilities of medical record officers regarding quantitative analysis of medical records and electronic medical records at Rumah Sakit Umum Hidayah Boyolali. The PkM implementation method includes material presentation, discussion, clinic and evaluation. The target of PkM consists of 13 medical record officers with the results of PkM being to increase the knowledge and ability of officers in analyzing the completeness of filling in medical records and electronic medical records.